Psychometric Evaluation of the Mental Health Continuum–Short Form in French Canadian Young Adults. (April 2017) - Doré, Isabelle; O'Loughlin, Jennifer L.; Sabiston, Catherine M.; Fournier, Louise
Objective: To examine the factor structure, internal consistency, reliability, sex invariance, and discriminant validity of the French Canadian version of the Mental Health Continuum–Short Form (MHC-SF). Method: A total of 1485 French-speaking postsecondary students in Quebec, Canada (58% female; mean age = 18.4, SD = 2.4), completed the MHC-SF. Confirmatory factor analysis (CFA) was used to assess the factorial structure of the MHC-SF. Internal consistency was assessed with Cronbach's alpha, and reliability was assessed with the rho reliability coefficient. Invariance testing across sex was conducted using multigroup CFA comparing 4 increasingly restrictive models, and discriminant validity was examined against the Hospital Anxiety and Depression Scale (HADS) using Pearson correlation coefficients and CFA. Results: CFA supported the correlated 3-factor structure of the MHC-SF, with emotional, social, and psychological well-being subscales. The scale and each subscale items had internal consistency coefficients (Cronbach's alphas) above .70 and reliability coefficients (Jöreskog's rho) ranging from .79 to .90. Based on the multigroup CFA, configural, metric, scalar, and error variance invariance of the MHC-SF was observed across sex. Finally, the 2-continua model, suggesting that mental health and mental illness are distinct but related dimensions, was supported by both moderate inverse correlations between MHC-SF and HADS subscale scores and the 2-factor structure in CFA. Conclusions: These data support the multidimensional structure of the MHC-SF and provide evidence of internal consistency, reliability, and invariance across sex. The MHC-SF is a valid and reliable measure of mental health that is distinct from mental illness among French Canadian young adults.